Distribution of Population of Immature Stages of Pear Psylla, Cαcopsyllα pyri, within the Tree and Development of Sampling Strategy - Stratopoulou, E. T.; Kapatos, E. T. (ENTOMOLOGIA HELLENICA, 1992)
The distribution of Cacopsylla pyri (L.) (Homoptera-Psyllidae) infestation within the tree canopy and in the varions organs of the tree was investigated in the region of Magnesia (Greece) during 1988 and 1989. The upper parts of the tree canopy and the sections orientated to South and west were infested heavier during winter and spring. Later in the scason the infestation was diffused within the tree canopy and at the end of the season a rather uniform pattern of distribution was observed. During the first oviposition period (February-March), the preferred oviposition sites were flower buds white during spring (second generation) they were the leaves of flower buds and young shoots. Sampling strategy for the study of populations of immature stages of pear psylla is discussed on the oasis of these findings.